2017
DOI: 10.1556/2006.6.2017.074
|View full text |Cite
|
Sign up to set email alerts
|

Established risk factors for addiction fail to discriminate between healthy gamers and gamers endorsing DSM-5 Internet gaming disorder

Abstract: Background and aimsThe DSM-5 includes criteria for diagnosing Internet gaming disorder (IGD) that are adapted from substance abuse and widely used in research and clinical contexts, although evidence supporting their validity remains scarce. This study compared online gamers who do or do not endorse IGD criteria regarding self-control-related abilities (impulsivity, inhibitory control, and decision-making), considered the hallmarks of addictive behaviors.MethodA double approach was adopted to distinguish patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 58 publications
6
60
1
Order By: Relevance
“…However, three of the four LCA groups exhibited elevated scores for the “preoccupation” item, suggesting that its diagnostic usefulness is limited. Consequently, our findings provide partial support for earlier studies (e.g., Charlton & Danforth, ; Deleuze, Nuyens, Rochat, Rothen, Maurage & Billieux, ) that suggested that some criteria from the IGD framework (e.g., preoccupation and tolerance) are probably not suitable for distinguishing between high but healthy engagement with digital games on the one hand and excessive and problematic engagement on the other. In keeping with these results, Deleuze et al .…”
Section: Discussionsupporting
confidence: 78%
“…However, three of the four LCA groups exhibited elevated scores for the “preoccupation” item, suggesting that its diagnostic usefulness is limited. Consequently, our findings provide partial support for earlier studies (e.g., Charlton & Danforth, ; Deleuze, Nuyens, Rochat, Rothen, Maurage & Billieux, ) that suggested that some criteria from the IGD framework (e.g., preoccupation and tolerance) are probably not suitable for distinguishing between high but healthy engagement with digital games on the one hand and excessive and problematic engagement on the other. In keeping with these results, Deleuze et al .…”
Section: Discussionsupporting
confidence: 78%
“…As found in other studies, the preoccupation [58,59,62] and escape [58,59,61,63] criteria had lower discriminatory power than the other items did. The deceiving others item had good discriminant capacity in the present study and others [59], whereas some authors found low diagnostic accuracy for this criterion [63].…”
Section: Reappraisal Of the Igd Criteria Using The Gas As A Proxysupporting
confidence: 80%
“…The following 5 criteria are more controversial: -Preoccupation (being absorbed by gaming and thinking about it): This criterion, thought to be related to cognitive salience, is considered a core criterion by some authors [30,61] but not others [20,58,62]. Preoccupation is commonly reported among high achievers [26,63] and is supposed to be common for gamers because of the social features of the games and flow-related engagement [62,64].…”
Section: The Igd Criteria Debatementioning
confidence: 99%
See 2 more Smart Citations